Accompagnement à la scolarité et mobilité - Benoît Larbiou (Sociétés et Jeunesses en Difficulté)
Since twenty years, the mobilization of school’s partners (through the plan – dispositif - of scholar’s accompaniment) next to school hides the real reasons which justify the necessity of this mobilization. Also, this mobilization doesn’t settle the problem of the accompanying adults’ position and the properties of their appointment. Instances outside the school encounter same difficulties to define why accompaniment is, for some children, necessary. Thereby, disappears the meaning of accompaniment.Ultimately, this dispositif responds to the necessity to find scholar solution to the social problem of maintain in school individuals which are socially no-disposed to stay in school. In order to manage the difficult environments, agents of instances outside the schools become school’s “objective allies” to adapt children and their family to scholar mode of socialization, to their forms and this culture. These mobilized agents became agents of “scholar proselytism”. The dispositif makes sure that they adhere to the doxa of “scholar mode of socialization”, that they respect the idea that any “action on society [comes through] pedagogic intervention”, that any solution to school’s problem must be find in scholar’s order.  The dispositif tries to regulate “struggle for partnership” between schools and instances outside the school. The different accompanying adults’ positions explain adhesion as inflection to this doxa. According to these different positions and to these different points of view, a repertory of practices and meanings of accompaniment is structured.